UPAYA PENINGKATAN EFEKTIVITAS PEMBELAJARAN PENJAS DI SD SAMIRONO BERDASARKAN KURIKULUM BERBASIS KOMPETENSI - Suhadi Suhadi (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
This research covers efforts in improving physical education learning process for 4th grader based on competence based curriculum. The problems to be solved are 1) ineffective time consumtion, (2) lack of facilities and equipment including site limits, (3) the needs for better understanding and interpretation on the learning contents which is in line with Competence- Based Curriculum (CBC), (4) the affective aspects either from teachers or students is one of the impoertant factors for the succesful PE learning. This research is a classroom action research involving two cycles. The research took place in at the Faculty of Sports Science, Yogyakarta State University, once per week from July to September 2005-2006. A number of 34 students were participated. They were at the 4th grade consisting of 16 boys and 18 girls. The action of the research is teaching PE using Curriculum 2004 employing CBC. The contents consisted of basic movements in PE, gymnastics, and traditional games. It took 50 minutes every single unit teaching learning. The results showed that there was improvement on the effectiveness of learning process, on the students motivation, and also students physical fitness. Kata Kunci: Pendidikan Jasmani, Efektivitas, Pembelajaran, KBK. . Kata Kunci: Pengembangan Multimedia Interaktif, Mata Kuliah Pendidikan Kesehatan Sekolah